2019
DOI: 10.1007/978-3-030-35333-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Technical Debt and Waste in Non-functional Requirements Documentation: An Exploratory Study

Abstract: Background: To adequately attend to non-functional require-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
11
0
5
Order By: Relevance
“…Although there are studies that investigate documentation in ASD [6,15,21,28,[33][34][35], those that specifically examine the documentation of QRs are few. Additionally, detailed investigation of practices of documentation of QRs in ASD is missing.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are studies that investigate documentation in ASD [6,15,21,28,[33][34][35], those that specifically examine the documentation of QRs are few. Additionally, detailed investigation of practices of documentation of QRs in ASD is missing.…”
Section: Related Workmentioning
confidence: 99%
“…They identified that the lack of QRs identification and the lack of information were related to high proportions of documentation debt. Robiolo et al [28], explored the indicators of technical debt and waste resulting from QR documentation based on survey findings.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Los requisitos no funcionales son restricciones en los servicios o funciones que ofrece el sistema, incluyendo restricciones de tiempo, restricciones en los procesos y estándares de desarrollo [3]. Algunos autores reconocen prácticas relacionadas con requisitos no funcionales [1]- [10], pero para nombrarlas emplean diferentes elementos: productos de trabajo y descripciones completas de funcionamiento [4], [5], restricciones [6] y nombres de métodos [7]. En otros casos emplean verbos junto con sustantivos [4], [6]- [10].…”
Section: Introductionunclassified
“…Algunos autores reconocen prácticas relacionadas con requisitos no funcionales [1]- [10], pero para nombrarlas emplean diferentes elementos: productos de trabajo y descripciones completas de funcionamiento [4], [5], restricciones [6] y nombres de métodos [7]. En otros casos emplean verbos junto con sustantivos [4], [6]- [10]. Barón [11] establece que una práctica bien nombrada en ingeniería de software debería contener un verbo nominalizado, un sustantivo y un adjetivo que identifique la forma en que se realiza la acción que se define con el verbo nominalizado.…”
Section: Introductionunclassified